Growth and development of Easter lily in response to container substrate with biochar. Issue 1 (2nd January 2019) - Guo, Yanjun; Niu, Genhua; Starman, Terri; Gu, Mengmeng
ABSTRACT: A greenhouse study was conducted to evaluate the growth and flowering of Easter lily ( Lilium longiflorum Thunb. ) grown in a commercial substrate (Sunshine Mix #1) amended with biochar at 0 (control), 20, 40, 60, or 80% (by volume) and fertigated at four different regimes (constant feeding at 200 or 300 mg L −1  N, or at every third watering with 200 or 300 mg L −1  N). The experimental design was a split-plot design with fertigation regime as the main plot and the biochar percentage as the subplot. There was no interaction between fertigation regime and the biochar percentage on growth or development parameters. Neither fertigation regime nor the biochar percentage affected the number of days before full flower, the number of flowers, total shoot dry weight, the number of leaves, and leaf gas exchange rate. Plants grown in 80% biochar had the highest ratio of stem length with green leaves to total stem length. Plants in the two constant feeding groups had higher SPAD readings than those fertigated at every third watering in week 17. In summary, up to 80% biochar could be used as a component to peat-based container substrate without significant changes in Easter lily growth and development.